SAFETY CLIMATE TO PSYCHOLOGICAL WELLBEING ON CIVILIAN PILOT IN INDONESIA - AGUSTINA, AMILYA; I MUSTOPO, WIDURA; S SABARGUNA, BOY; WANGGE, GRACE; SOSROSUMIHARDJO, DANARDI (Innovare Journal of Social Sciences, 2021)
Objective: Psychological wellbeing of the pilot can affect the flight cognitive function of the pilot, thus endangering the safety of the flight. The level of wellbeing of the pilots is related to the safety climate of the pilot. The purpose of this study is to determine the relationship between the safety climate and psychological wellbeing of civilian pilot in Indonesia. Methods: This was an analytic study using cross-sectional method. The sample was determined by consecutive sampling technique. Data were collected by filling out questionnaires by subjects regarding the variables of the safety climate and psychological wellbeing. The data analysis used was multiple linear regression. Results: The safety climate has a significant effect on psychological wellbeing (ß=0.921). The dimensions of the safety climate which have a significant effect are management (ß=0.135), safety systems (ß=0.143), procedures (ß=0.176), training (ß=0.153), communication (ß=0.232), and operations personnel (ß=0.185). Conclusion: Management, safety systems, procedures, training, communication, and operations personnel have significant effects on psychological wellbeing of civilian pilot in Indonesia.